Chemical constituents from the root bark of Dictamnus dasycarpus Turcz. (Rutaceae) and their chemotaxonomic significance. (October 2019) - Zhang, Jin-Ling; Song, Shang-Chun; Liu, Ji-Cheng; Ni, Peng-Hui; Liu, Lei; Ma, Yu-Kun; Sun, Yu; Liu, Qi; Guo, Li-Na
Abstract: This work described the isolation and characterization of seven compounds from Dictamnus dasycarpus Turcz., including one new ester, (2 R )-4-(2, 2-dimethyl-5-oxotetrahydrofuran-3-yl)-2-hydroxypent-3-anoic acid ethyl ester (1 ); and six known glycosides (2 –7 ). The structure of compound1 was elucidated on the basis of extensive spectral analyses, including IR, HR-ESIMS, 1D and 2D NMR (NOESY, HMBC and HSQC). All these compounds were described here for the first time from the genus Dictamnus . Moreover, the results provide further information about the diversity of compounds in the genus Dictamnus . Highlights: A new compound is isolated from the root bark of Dictamnus dasycarpus Turcz. Compounds1 –7 are herein reported for the first time from the genus Dictamnus. Compounds1, 3 and5 –7 have not previously been recorded in the family Rutaceae. This study extends the chemical knowledge about the constituents of family Rutaceae.